2018
DOI: 10.22581/muet1982.1804.20
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Incorporating Induction Furnace Slag in Concrete as Replacement of Cement: A Case Study of Pakistan

Abstract: As Pakistan along with the rest of the world continues to develop, demand for limited natural resources continues to increase also. This demand for resources and subsequent waste that is generated has driven the idea of sustainability towards the forefront of modern day research. To achieve this goal, new and innovative ways are being developed to recycle waste materials that otherwise would end up in landfill sites. Slag, a by-product of steel manufacturing is one such waste material. Pakistan as being a deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The outcome of this research can be used for the evaluation of the effect of local waste mineral admixtures found in Pakistan on the properties of plain and fiber-reinforced concrete. A variety of natural and waste mineral admixtures are cheaply available in Pakistan, e.g., bentonite, metakaolin, rice husk ash, slag, fly ash, and silica fume [13,[55][56][57], but there is a lack of published information on the properties of these mineral admixtures in normal and fiber-reinforced concrete. To cope with the rising climate changes in Pakistan and surrounding regions, it is necessary to reduce the reliance of the concrete industry on cement production by supplementing the demand for cement with supplementary mineral admixtures.…”
Section: Research Significancementioning
confidence: 99%
“…The outcome of this research can be used for the evaluation of the effect of local waste mineral admixtures found in Pakistan on the properties of plain and fiber-reinforced concrete. A variety of natural and waste mineral admixtures are cheaply available in Pakistan, e.g., bentonite, metakaolin, rice husk ash, slag, fly ash, and silica fume [13,[55][56][57], but there is a lack of published information on the properties of these mineral admixtures in normal and fiber-reinforced concrete. To cope with the rising climate changes in Pakistan and surrounding regions, it is necessary to reduce the reliance of the concrete industry on cement production by supplementing the demand for cement with supplementary mineral admixtures.…”
Section: Research Significancementioning
confidence: 99%
“…Utilizing these slags in the construction industry will both reduce the cost of storage and enable more efficient use of natural resources [31]. Although slag has a high iron oxide content, it can't be used in cement production.…”
Section: Introductionmentioning
confidence: 99%
“…Concrete structures are susceptible to crack development mainly due to early-age shrinkage and loading conditions. Scientific studies revealed that the service life and performance of concrete is reduced due to crack formation/growth, through which water, Clions and CO2 gas penetrates resulting in the replacement of cement [3], use of wood waste to enhance the echo efficiency of cement [4], the role of steel fibers to enhance mechanical properties of concrete [5], cracking of clay beams that can replace concrete beams [6] and effect of treated wastewater on the strength of concrete [7].…”
Section: Introductionmentioning
confidence: 99%